Igneous rocks - Fretland VanVoorst, Jenny, 1972- (Blastoff! discovery. Rocks & minerals., 2020)
Describes igneous rocks, and discusses how they form and how they are used today. Includes rock profiles, an activity, color photographs, a glossary, and further resources.